Genome-wide identification of terpenoid synthase family genes in Gossypium hirsutum and functional dissection of its subfamily cadinene synthase A in gossypol synthesis - Wen, Tianyang; Xu, Xiao; Ren, Aiping; Zhao, Ge; Wu, Jiahe (Frontiers in Plant Science, 2023)
Plant terpenoid synthase (TPS) family genes participate in metabolites synthesis, e.g., hormones and gossypol. Here, we genome-widely identified TPS family genes in 12 land plant species. 413 TPS-related genes were divided into 7 subfamilies. The TPS-c in Bryophytes was suggested to be the earliest subfamily followed by TPS-e/f and TPS-h presence in fern; and TPS-a, a largest number of genes, were derived in monocotyledonous and dicotyledonous. Collinearity analysis showed that 47 out of 61 TPS genes in G. hirsutum were collinear within G. arboreum and G. raimondii. 25 GhTPS-a genes belong to cadinene synthase (GhCDN) subfamily, and were divided into five groups, A, B, C, D and E. The special cis-elements in promoters of 15 GhCDN-A genes suggested that JA and ethylene signaling pathway may involve in their expression regulation. When 15 GhCDN-A genes were simultaneously silenced through virus induced gene silencing method, glandular color of GhCDN-A-silenced plants was lighter than that of the control, supported by gossypol content decrease based on HPLC testing, suggesting that GhCDN-A subgroup genes participate in gossypol synthesis. According to RNA-seq analysis, gossypol synthesis-related genes and disease resistant genes in the glandular variety exhibited upregulated expression compared to no glandular variety, whereas hormones signaling-related genes were downregulated. In all, these results reveal plant TPS genes evolution rules, and dissected the TPS subfamily, GhCDN-A, function in gossypol synthesis in cotton.